Geographical Indications: Agricultural Perspectives with Special Reference to Rice Genetic Resources in India: Geographical Indications and Rice Genetic Resources - Goyal, Vishnu Kumar; Singh, Rakesh; Singh, Gyanendra Pratap (Journal of Cereal Research, 2025)
Geographical Indications (GIs) have gained significant momentum to conserve local biodiversity, traditional knowledge and to promote local trade. A total of 696 GI shave been registered in India till July 2025, out of which 94.5% were domestic in nature.The handicraft goods stood first, accounting for 52.4%, followed by agricultural (31.5%), manufactured (7.9%) and food stuffs (7.8%). During the past 20 years, a total of 219 agricultural GIs have been registered in 73 agricultural crops and commodities in the country. These are quite diversified, including banana, brinjal, chilli, litchi, malta, mango, rice, sea buckthorn, sorghum tea, etc. The highest agricultural GIs were granted during the year 2023-24 (49). State-wise, Maharashtra ranked first with 38 agricultural GIs in force, followed byTamil Nadu (22), Karnataka & Kerala (21 each) and Uttarakhand (15). The traditional knowledge in rice culminated in to the highest agricultural GI registrations (31), followed by mango & chilli (16 each) and banana (8), etc. Kerala ranked first with 06 GIsfor rice genetic resources, followed by West Bengal (04), Assam & Maharashtra (03 each). The “Navara Rice” and “Palakkadan Matta Rice” have been reported with medicinal properties, whereas “Pokkali Rice”, “Ambemohar Rice” and “Karen Musley Rice” have tolerance to salinity coupled with distinct aroma and quality characters. The “Jeera phool” and “Balaghat Chinoor” from central India are more suited for kheer preparation. In the realm of trade, farmers, tribes and communities traditionally engaged in biodiversity conservation can be sensitized for GI boosting, enabling them to fetch higher market prices and recognition.